2019
DOI: 10.1007/s10120-019-00927-x
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet adherence and risk of esophageal and gastric cancer subtypes in the Netherlands Cohort Study

Abstract: Background Mediterranean diet (MD) adherence has been associated with reduced risks of esophageal and gastric cancer (subtypes) in a limited number of studies. We prospectively investigated associations between MD adherence and risks of esophageal squamous cell carcinoma (ESCC), esophageal adenocarcinoma (EAC), gastric cardia adenocarcinoma (GCA), and gastric non-cardia adenocarcinoma (GNCA) in a Dutch cohort. Methods Analyses were conducted using data from the 120852 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 51 publications
4
48
0
Order By: Relevance
“…Although our results suggested a small reduction in overall cancer risk for alcohol intake within the range, compared to higher alcohol consumption, the benefit from light-to-moderate consumption of wine on cancer risk in observational studies is inconclusive [174][175][176]. Risk estimates for several cancers based on MedDiet scores including alcohol did not differ from those simply adjusted for total alcohol intake [122,[145][146][147][148][149]. Consumption of wine together with meals is a part of the cultural heritage in Mediterranean countries, but it is less common in other countries [177].…”
Section: Discussionmentioning
confidence: 53%
“…Although our results suggested a small reduction in overall cancer risk for alcohol intake within the range, compared to higher alcohol consumption, the benefit from light-to-moderate consumption of wine on cancer risk in observational studies is inconclusive [174][175][176]. Risk estimates for several cancers based on MedDiet scores including alcohol did not differ from those simply adjusted for total alcohol intake [122,[145][146][147][148][149]. Consumption of wine together with meals is a part of the cultural heritage in Mediterranean countries, but it is less common in other countries [177].…”
Section: Discussionmentioning
confidence: 53%
“…34). Because of the equal or better performance of aMEDr compared with mMEDr in both the current and previous NLCS analyses (35)(36)(37), the Results section of this article mainly focuses on associations with aMEDr and subgroup analyses were only performed using this score. We preferred the aMED variant without alcohol (aMEDr), because alcohol consumption is a risk factor for several types of cancer (29).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…However, findings from a prospective study demonstrated approximate reductions of 40% in the risk of gastric cancer [ 8 ] and 50% in the risk of esophageal cancer [ 9 ], when consuming a high-quality diet defined by the DII. Likewise, others have reported beneficial effects on the risk of UGI cancer when consuming high-quality diets, as measured by the MDS [ 10 , 11 ] and HEI [ 12 ].…”
Section: Introductionmentioning
confidence: 99%